Rubber composition and conveyor belt
By adding a specific proportion of ingredients to the rubber composition, an excellent rubber composition is formed, which solves the problem of insufficient wear resistance and flame retardancy of the existing rubber composition after curing, and achieves excellent performance after initial and aging.
Patent Information
- Application Number
- CN202411097893.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-13
- Filing Date
- 2024-08-12
- Publication Date
- 2025-04-15
AI Technical Summary
After curing, the initial wear resistance and flame retardancy of the existing rubber composition may be insufficient, and the physical properties cannot be effectively maintained after aging.
An excellent rubber composition is formed by adding a specific proportion of natural rubber, butadiene rubber, chlorinated paraffin wax, antimony trioxide, trimethyldihydroquinoline compound or diphenylamine compound with a weight average molecular weight of 300 or more to the rubber composition.
The initial wear resistance and flame retardancy of vulcanized rubber are achieved, and excellent wear resistance and flame retardancy are maintained in terms of physical properties after aging.
Smart Images

Figure BDA0004988516300000081 
Figure BDA0004988516300000091 
Figure BDA0004988516300000181
Abstract
Description
Technical Field
[0001] The present invention relates to a rubber composition and a conveyor belt. Background Art
[0002] Conventionally, there is known a rubber composition for a conveyor belt containing natural rubber, butadiene rubber, chlorinated paraffin, antimony trioxide, a vulcanizing agent, and the like (for example, Patent Documents 1 and 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 7182853
[0006] Patent Document 2: Japanese Patent No. 6620105 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The present inventors have studied the rubber compositions disclosed in Patent Documents 1 and 2, and have come to realize that the vulcanized rubber obtained by curing such rubber compositions sometimes has problems such as poor initial wear resistance or flame retardancy, or physical properties after aging (wear resistance, mechanical properties, and flame retardancy after aging. The same applies to physical properties after aging hereinafter) cannot maintain the initial properties.
[0009] Therefore, an object of the present invention is to provide a rubber composition which is excellent in maintaining the initial wear resistance, initial flame retardancy, and physical properties after aging of the obtained vulcanized rubber.
[0010] Furthermore, the present invention also aims to provide a conveyor belt.
[0011] Means for solving problems
[0012] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that the problems can be solved by the following configuration.
[0013] [1] A rubber composition comprising: a diene rubber comprising natural rubber and butadiene rubber, a flame retardant comprising chlorinated paraffin and antimony trioxide, an amine compound comprising a trimethyldihydroquinoline compound having a weight average molecular weight of 300 or more and / or a diphenylamine compound having a molecular weight of 300 or more, carbon black, sulfur, and a vulcanization accelerator;
[0014] The content of the natural rubber is 30 to 60% by mass of the total amount of the diene rubber.
[0015] The content of the butadiene rubber is 40 to 70% by mass of the total amount of the diene rubber.
[0016] The content of the chlorinated paraffin is 20 to 35 parts by mass based on 100 parts by mass of the diene rubber.
[0017] The content of the antimony trioxide is 5 to 12 parts by mass based on 100 parts by mass of the diene rubber.
[0018] The mass ratio of the content of the amine compound relative to 100 parts by mass of the diene rubber / the amount of chlorine in the chlorinated paraffin relative to 100 parts by mass of the diene rubber is 0.10 to 0.60.
[0019] [2] The rubber composition according to [1], wherein the content of the natural rubber is 40 to 55% by mass of the total amount of the diene rubber.
[0020] The content of the butadiene rubber is 45 to 60% by mass in the total amount of the diene rubber.
[0021] [3] The rubber composition according to [1] or [2], wherein the carbon black has a nitrogen adsorption specific surface area exceeding 100 m 2 / g and the oil absorption of dibutyl phthalate is 100~140cm 3 / 100g of carbon black 1.
[0022] [4] The rubber composition according to any one of [1] to [3], wherein the content of the carbon black is 40 to 60 parts by mass based on 100 parts by mass of the diene rubber.
[0023] [5] The rubber composition according to any one of [1] to [4], wherein the content of the chlorinated paraffin is 23 to 30 parts by mass based on 100 parts by mass of the diene rubber.
[0024] The content of the antimony trioxide is 5 to 10 parts by mass based on 100 parts by mass of the diene rubber.
[0025] [6] The rubber composition according to any one of [1] to [5], wherein the amine compound includes the trimethyldihydroquinoline compound.
[0026] [7] The rubber composition according to any one of [1] to [6], further comprising an antioxidant.
[0027] [8] The rubber composition according to any one of [1] to [7], which is for conveyor belts.
[0028] [9] A conveyor belt produced using the rubber composition according to any one of [1] to [8].
[0029] Effects of the Invention
[0030] According to the present invention, it is possible to provide a rubber composition in which the obtained vulcanized rubber is excellent in maintaining initial wear resistance, initial flame retardancy, and physical properties after aging.
[0031] Furthermore, the present invention may also provide a conveyor belt. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a cross-sectional view of one embodiment of the conveyor belt of the present invention.
[0033] Figure 2 This is a cross-sectional view of another embodiment of the conveyor belt of the present invention. DETAILED DESCRIPTION
[0034] Hereinafter, the present invention will be described in detail.
[0035] Although the description of the constituent elements described below may be made based on representative embodiments of the present invention, the present invention is not limited to such embodiments.
[0036] In the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to".
[0037] In the present specification, each component contained in the rubber composition of the present invention can be used alone or in combination of two or more.
[0038] In the present specification, when the rubber composition of the present invention contains two or more components in combination, the "content" of the component means the total content of the two or more components unless otherwise specified.
[0039] In the present specification, the production method of each component is not particularly limited unless otherwise specified, and examples thereof include conventionally known methods.
[0040] In the present specification, the fact that the obtained vulcanized rubber has more excellent at least one of initial abrasion resistance, initial flame retardancy, and maintenance of physical properties after aging is also referred to as “the effect of the present invention is more excellent”.
[0041] [Rubber composition]
[0042] The rubber composition of the present invention is the following rubber composition, comprising:
[0043] A diene rubber comprising natural rubber and butadiene rubber, a flame retardant comprising chlorinated paraffin and antimony trioxide, an amine compound comprising a trimethyldihydroquinoline compound having a weight average molecular weight of 300 or more and / or a diphenylamine compound having a molecular weight of 300 or more, carbon black, sulfur, and a vulcanization accelerator,
[0044] The content of the natural rubber is 30 to 60% by mass of the total amount of the diene rubber.
[0045] The content of the butadiene rubber is 40 to 70% by mass of the total amount of the diene rubber.
[0046] The content of the chlorinated paraffin is 20 to 35 parts by mass based on 100 parts by mass of the diene rubber.
[0047] The content of the antimony trioxide is 5 to 12 parts by mass based on 100 parts by mass of the diene rubber.
[0048] The mass ratio of the content of the amine compound relative to 100 parts by mass of the diene rubber / the amount of chlorine in the chlorinated paraffin relative to 100 parts by mass of the diene rubber is 0.10 to 0.60.
[0049] The reason why the rubber composition of the present invention having the above-mentioned structure can solve the problem of the present invention is not necessarily clear, but the present inventors speculate as follows. It should be noted that the mechanism of obtaining the effect is not limited by the following speculation. In other words, the situation where the effect is obtained by a mechanism other than the following is also included in the scope of the present invention.
[0050] The present inventors have confirmed that the wear resistance of the vulcanized rubber obtained by increasing the content ratio of butadiene rubber (BR) in the diene rubber is improved, but there is a tendency for the flame retardancy to deteriorate. For the deterioration of the flame retardancy, the increase of the flame retardant is considered to be a countermeasure, but the present inventors have also confirmed that the increase of the flame retardant has a tendency to deteriorate the physical properties after aging, including the wear resistance.
[0051] Generally, chlorinated paraffin, which is one type of flame retardant, is easily decomposed under heating conditions. Therefore, when a conveyor belt that is expected to be used outdoors for a long time contains chlorinated paraffin as a flame retardant, there is a concern that the flame retardancy of the conveyor belt will decrease as the conveyor belt is used for a long time.
[0052] Furthermore, it is considered that the vulcanized rubber is degraded by chlorine radicals and the like generated by the decomposition of the chlorinated paraffin, and the wear resistance and mechanical properties are reduced over time.
[0053] On the other hand, in the present invention, the physical properties of the obtained vulcanized rubber after aging can be maintained at an excellent level.
[0054] The present inventors presume that this is because the predetermined amine compound (an amine compound including a trimethyldihydroquinoline compound having a weight average molecular weight of 300 or more and / or a diphenylamine compound having a molecular weight of 300 or more) contained in the rubber composition of the present invention inhibits the decomposition of chlorinated paraffin.
[0055] In the present invention, it is considered that the physical properties after aging can be maintained at an excellent level by setting the mass ratio of the content of the amine compound / the amount of chlorine in the chlorinated paraffin to be within a specific range.
[0056] [Diene rubber]
[0057] In the present invention, the diene rubber contained as the rubber component is a polymer formed by containing a monomer of a conjugated diene compound.
[0058] In the present invention, the diene rubber includes natural rubber and butadiene rubber.
[0059] [Natural rubber]
[0060] In the present invention, the natural rubber (NR) included as the diene rubber is not particularly limited, and examples thereof include conventionally known ones.
[0061] [Butadiene rubber]
[0062] In the present invention, the butadiene rubber (BR) included as the diene rubber is not particularly limited, and examples thereof include conventionally known ones.
[0063] As one of the preferred embodiments, BR is, for example, polybutadiene which is solid at 23° C. In addition, BR may be unmodified BR or modified BR.
[0064] From the viewpoint of achieving better effects of the present invention (particularly, maintenance of initial wear resistance and physical properties after aging (particularly wear resistance)), the weight average molecular weight of BR is preferably 200,000 or more, more preferably 300,000 to 1,000,000.
[0065] In the present specification, the weight average molecular weight (Mw) of BR may be a standard polystyrene conversion value obtained by gel permeation chromatography (GPC) measurement under the following conditions.
[0066] Solvent: Tetrahydrofuran
[0067] Detector: RI detector
[0068] [Natural rubber content]
[0069] In the present invention, the content of the natural rubber is 30 to 60% by mass of the total amount of the above-mentioned diene rubber.
[0070] From the viewpoint of further improving the effects of the present invention, the content of natural rubber is preferably 40 to 55% by mass, more preferably 40 to 52% by mass, and even more preferably 40 to 50% by mass, based on the total amount of the diene rubber.
[0071] [Content of butadiene rubber]
[0072] In the present invention, the content of the butadiene rubber is 40 to 70% by mass in the total amount of the above-mentioned diene rubber.
[0073] From the viewpoint of achieving better effects of the present invention (particularly, maintenance of initial wear resistance and physical properties after aging (particularly wear resistance)), the content of the butadiene rubber is preferably 45 to 60% by mass, more preferably 48 to 60% by mass, and further preferably 50 to 60% by mass of the total amount of the diene rubber.
[0074] As one of the preferred embodiments, the diene rubber is preferably natural rubber or butadiene rubber.
[0075] ·Polymers other than diene rubber
[0076] The rubber composition of the present invention may further contain a polymer other than diene rubber (e.g., a polyolefin such as polytetrafluoroethylene, a silicone such as polydimethylsiloxane) as a rubber component in addition to the diene rubber, but the total content of natural rubber and butadiene rubber is preferably 80% by mass or more and 100% by mass or less, more preferably 90% by mass or more and 100% by mass or less, and further preferably 100% by mass in the total content of the diene rubber and the polymer other than diene rubber (i.e., in the total amount of the rubber component). It should be noted that the polymer other than diene rubber does not include a trimethyldihydroquinoline compound having a weight average molecular weight of 300 or more, which is an amine compound described later.
[0077] [Flame retardant]
[0078] The rubber composition of the present invention contains a flame retardant comprising chlorinated paraffin and antimony trioxide.
[0079] [Chlorinated paraffin]
[0080] In the present invention, the chlorinated paraffin contained as a flame retardant is a paraffin containing chlorine.
[0081] (Ratio of chlorine in chlorinated paraffin)
[0082] The proportion of chlorine in the chlorinated paraffin is not particularly limited, but is preferably 40 to 90% by mass, more preferably 60 to 90% by mass, in the chlorinated paraffin from the viewpoint of achieving better effects of the present invention (particularly initial flame retardancy).
[0083] [Content of chlorinated paraffin]
[0084] In the present invention, the content of the chlorinated paraffin is 20 to 35 parts by mass based on 100 parts by mass of the diene rubber.
[0085] From the viewpoint of achieving more excellent effects of the present invention (particularly maintenance of initial flame retardancy and physical properties after aging), the content of the chlorinated paraffin is preferably 23 to 30 parts by mass based on 100 parts by mass of the diene rubber.
[0086] [Amount of chlorine in chlorinated paraffin]
[0087] In the present invention, the amount of chlorine in the chlorinated paraffin relative to 100 parts by mass of the diene rubber can be obtained by multiplying the content of the chlorinated paraffin relative to 100 parts by mass of the diene rubber by the ratio of chlorine in the chlorinated paraffin (multiplication).
[0088] [Antimony trioxide]
[0089] In the present invention, antimony trioxide (Sb 2 O 3 ) contained as a flame retardant is not particularly limited.
[0090] [Antimony trioxide content]
[0091] In the present invention, the content of antimony trioxide is 5 to 12 parts by mass based on 100 parts by mass of the diene rubber.
[0092] From the viewpoint of achieving more excellent effects of the present invention, the content of antimony trioxide is preferably 5 to 10 parts by mass based on 100 parts by mass of the diene rubber.
[0093] [Amine compounds]
[0094] The rubber composition of the present invention contains an amine compound including a trimethyldihydroquinoline compound having a weight average molecular weight of 300 or more and / or a diphenylamine compound having a molecular weight of 300 or more.
[0095] (Trimethyldihydroquinoline compounds)
[0096] The amine compound contained in the rubber composition of the present invention may include a trimethyldihydroquinoline compound having a weight average molecular weight of 300 or more.
[0097] As the above-mentioned trimethyldihydroquinoline compounds, for example, polymers of 2,2,4-trimethyl-1,2-dihydroquinoline (compounds of the structure in [] in the following formula) shown in the following formula can be cited. It should be noted that the compounds shown in [] below are shown as monomers. The polymer of 2,2,4-trimethyl-1,2-dihydroquinoline refers to a polymer of 2,2,4-trimethyl-1,2-dihydroquinoline (monomer) or more. n (number of repeating units) in the following formula is 2 or more.
[0098]
[0099] (Weight average molecular weight of trimethyldihydroquinoline compounds)
[0100] In the present invention, the weight average molecular weight of the trimethyldihydroquinoline compound is 300 or more.
[0101] From the viewpoint of achieving more excellent effects of the present invention, the weight average molecular weight of the trimethyldihydroquinoline compound is preferably 1,000 or less.
[0102] In addition, in this specification, when the amine compound is a polymer like the above-mentioned trimethyldihydroquinoline compound, its molecular weight is represented by a weight average molecular weight.
[0103] In the present specification, when the amine compound is a polymer, the weight average molecular weight (Mw) thereof may be a standard polystyrene conversion value obtained by gel permeation chromatography (GPC) measurement under the following conditions.
[0104] Solvent: Tetrahydrofuran
[0105] Detector: RI detector
[0106] (Diphenylamine compounds)
[0107] The amine compound contained in the rubber composition of the present invention may include a diphenylamine compound having a molecular weight of 300 or more.
[0108] The diphenylamine compound is a compound having a structure in which two benzene rings are bonded via -NH-.
[0109] The diphenylamine compound may further have an amino group such as -NH2 or another -NH- group in addition to the -NH- group. However, one preferred embodiment is to have only the -NH- group in which two benzene rings are bonded as an amino group.
[0110] Examples of the diphenylamine compound include alkylated diphenylamine. The "alkylated" alkyl group in the alkylated diphenylamine may be bonded to at least one of the two benzene rings constituting the alkylated diphenylamine. The number of carbon atoms of the alkyl group is preferably 1 to 10. The diphenylamine compound may have two or more of the alkyl groups. When the diphenylamine compound has two alkyl groups, one alkyl group may be bonded to each of the two benzene rings.
[0111] Examples of the diphenylamine compound include di(alkylphenyl)amines, and specific examples thereof include octylated diphenylamine (the following structure).
[0112]
[0113] (Molecular weight of diphenylamine compound)
[0114] In the present invention, the molecular weight of the diphenylamine compound is 300 or more.
[0115] From the viewpoint of achieving more excellent effects of the present invention, the molecular weight of the diphenylamine compound is preferably 1,000 or less.
[0116] In addition, in this specification, when the amine compound is a monomer like the above-mentioned diphenylamine compound, the molecular weight is a general molecular weight.
[0117] In the present specification, when the amine compound is a monomer, the molecular weight thereof can be determined by calculation from the structural formula or by gas chromatography or the like.
[0118] From the viewpoint of achieving more excellent effects of the present invention (particularly, maintenance of initial wear resistance and physical properties after aging), the amine compound preferably includes the trimethyldihydroquinoline compound.
[0119] (Content of amine compounds)
[0120] From the viewpoint of achieving better effects of the present invention (particularly maintenance of initial wear resistance and physical properties after aging), the content of the amine compound is preferably 1.5 to 20 parts by mass, more preferably 1.5 to 3.0 parts by mass, based on 100 parts by mass of the diene rubber.
[0121] [Mass ratio of the content of amine compound / the amount of chlorine in chlorinated paraffin]
[0122] In the present invention, the mass ratio of the content of the amine compound relative to 100 parts by mass of the diene rubber / the amount of chlorine in the chlorinated paraffin relative to 100 parts by mass of the diene rubber is 0.10 to 0.60.
[0123] The above mass ratio can be expressed by the following formula.
[0124] Mass ratio=(content of the above-mentioned amine compound relative to 100 parts by mass of the diene rubber: unit is mass parts) / [(content of the above-mentioned chlorinated paraffin relative to 100 parts by mass of the diene rubber: unit is mass parts)×(ratio of chlorine in the above-mentioned chlorinated paraffin: unit is mass %) / 100]
[0125] The content of the amine compound relative to 100 parts by mass of the diene rubber, the content of the chlorinated paraffin relative to 100 parts by mass of the diene rubber, and the ratio (mass %) of chlorine in the chlorinated paraffin are as described above.
[0126] From the viewpoint of achieving more excellent effects of the present invention (particularly, maintenance of initial wear resistance and physical properties after aging), the mass ratio is preferably 0.11 to 0.20.
[0127] [Carbon black]
[0128] The rubber composition of the present invention contains carbon black.
[0129] The carbon black is not particularly limited, and examples thereof include ISAF grade carbon black and HAF grade carbon black.
[0130] From the viewpoint of achieving better effects of the present invention (particularly, maintaining initial wear resistance and physical properties after aging), the carbon black preferably contains a carbon black having a nitrogen adsorption specific surface area of more than 100 m 2 / g and the oil absorption of dibutyl phthalate is 100~140cm 3 / 100g of carbon black 1, more preferably comprising ISAF grade carbon black.
[0131] The nitrogen adsorption specific surface area (N2SA) of carbon black can be measured in accordance with JIS K6217-2:2017.
[0132] The dibutyl phthalate oil absorption (DBP) of carbon black can be measured in accordance with JIS K6217-4:2017.
[0133] (Carbon black content)
[0134] From the viewpoint of achieving more excellent effects of the present invention (particularly maintenance of initial wear resistance and physical properties after aging), the content of carbon black is preferably 40 to 60 parts by mass based on 100 parts by mass of the diene rubber.
[0135] When carbon black includes the carbon black 1, the content of the carbon black 1 may be at least a part of the content of the carbon black, and the carbon black 1 may be the entire amount of the carbon black.
[0136] [sulfur]
[0137] The rubber composition of the present invention contains sulfur.
[0138] Sulfur is not particularly limited as long as it is a substance used for vulcanization of rubber, and examples thereof include conventionally known substances.
[0139] From the viewpoint of achieving more excellent effects of the present invention, the sulfur content is preferably 0.5 to 5.0 parts by mass, more preferably 1.0 to 4.0 parts by mass, based on 100 parts by mass of the diene rubber.
[0140] [Vulcanization accelerator]
[0141] The rubber composition of the present invention contains a vulcanization accelerator.
[0142] The vulcanization accelerator is not particularly limited as long as it is a substance used for vulcanization of rubber. Examples of the vulcanization accelerator include benzothiazolylsulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazolylsulfenamide (CZ) and N-tert-butyl-2-benzothiazolylsulfenamide (NS); thiuram-based vulcanization accelerators such as tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); guanidine-based vulcanization accelerators such as diphenylguanidine (DPG); and sulfide-based vulcanization accelerators such as dibenzothiazyl disulfide (DM) and 4,4'-dithiomorpholine.
[0143] From the viewpoint of achieving better effects of the present invention (particularly maintenance of physical properties after aging) and excellent material processability (Mooney scorch), the vulcanization accelerator preferably contains a benzothiazolylsulfenamide-based vulcanization accelerator, and more preferably contains N-cyclohexyl-2-benzothiazolylsulfenamide (CZ).
[0144] From the viewpoint of achieving more excellent effects of the present invention (particularly maintenance of initial wear resistance and physical properties after aging), the content of the vulcanization accelerator is preferably 0.5 to 8.0 parts by mass based on 100 parts by mass of the diene rubber.
[0145] More preferably, the content of the vulcanization accelerator is 0.5 to 8.0 parts by mass based on 100 parts by mass of the diene rubber, and the mass ratio of the content of the vulcanization accelerator based on 100 parts by mass of the diene rubber / the content of sulfur based on 100 parts by mass of the diene rubber is 1 to 10.
[0146] (Antioxidant)
[0147] The rubber composition of the present invention preferably further contains an antioxidant.
[0148] The antioxidant does not contain the above-mentioned amine compounds.
[0149] The antioxidant is not particularly limited, but preferably contains an amine antioxidant, and more preferably contains N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6C).
[0150] The content of the antioxidant is preferably 0.5 to 8.0 parts by mass based on 100 parts by mass of the diene rubber.
[0151] (additive)
[0152] The rubber composition of the present invention may further contain additives in addition to the above-mentioned components. Examples of the additives include wax, zinc oxide, stearic acid, oil, and vulcanization retarders (eg, N-cyclohexylthiophthalimide).
[0153] (Manufacturing method)
[0154] The method for producing the rubber composition of the present invention is not particularly limited, and one example includes a method in which the essential components and additives that may be further used as needed are mixed at 90 to 180° C. using a Banbury mixer or the like.
[0155] (vulcanization)
[0156] The vulcanization of the rubber composition of the present invention can be carried out under the conditions usually performed. The vulcanization temperature can be, for example, 120 to 180° C. During the vulcanization, pressure may be applied.
[0157] (use)
[0158] As an application of the rubber composition of the present invention, for example, a rubber composition for conveyor belts can be mentioned.
[0159] [conveyor]
[0160] The conveyor belt of the present invention is a conveyor belt produced using the rubber composition of the present invention.
[0161] The rubber composition used for the conveyor belt of the present invention is not particularly limited as long as it is the rubber composition of the present invention.
[0162] The conveyor belt of the present invention is not particularly limited except that it is produced using the rubber composition of the present invention.
[0163] Since the conveyor belt of the present invention is produced using the rubber composition of the present invention, it is excellent in initial wear resistance, initial flame retardancy, and maintenance of physical properties after aging.
[0164] There is no particular limitation on which component of the conveyor belt of the present invention the rubber composition of the present invention is applied to. The rubber composition of the present invention can be used to manufacture all or part of the rubber constituting the conveyor belt of the present invention.
[0165] Since the vulcanized rubber obtained by curing the rubber composition of the present invention is excellent in initial wear resistance, initial flame retardancy, and maintenance of physical properties after aging, the conveyor belt of the present invention having a covering rubber formed using the rubber composition of the present invention can be cited as one of the preferred embodiments.
[0166] Embodiments of the conveyor belt of the present invention will be described below using the accompanying drawings. It should be noted that the present invention is not limited to the accompanying drawings.
[0167] Figure 1 This is a cross-sectional view of one embodiment of the conveyor belt of the present invention. Figure 1One embodiment of the conveyor belt of the present invention shown (herein, also referred to as the first embodiment of the conveyor belt of the present invention) is a conveyor belt 4 in which a fabric layer 1 is coated with a coating rubber (adhesive rubber) 2 to form a core material layer, and the outer periphery thereof is covered with a covering rubber 3. The covering rubber 3 is preferably formed using the rubber composition of the present invention.
[0168] exist Figure 1 In the embodiment, the conveyor belt 4 has the fabric layer 1 as the core material, and the number of laminated layers of the fabric layer 1, the thickness of the covering rubber 3, the belt width, etc. can be appropriately determined according to the purpose of use.
[0169] Examples of the cloth layer include canvas made of woven fabric of synthetic fibers such as nylon, vinylon, and polyester.
[0170] The thicknesses T1 and T2 of the cover rubber 3 may be approximately 1.5 to 20 mm, respectively, under normal circumstances.
[0171] In addition, coating rubber 2 can use coating rubber used for known conveyor belts. As the coating rubber, for example, a rubber composition containing natural rubber (NR), nitrile rubber (NBR), styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR), ethylene-propylene rubber (EPT), ethylene-propylene-diene rubber (EPDM), etc. as a rubber component can be used.
[0172] Next, use Figure 2 A second embodiment of the conveyor belt of the present invention will be described.
[0173] Figure 2 This is a cross-sectional view of another embodiment of the conveyor belt of the present invention.
[0174] like Figure 2 As shown, the second embodiment of the conveyor belt of the present invention is a conveyor belt 8 in which a steel cord 5 is coated with a cushion rubber (adhesive rubber) 6 to form a core layer, and the outer periphery thereof is covered with a covering rubber 7. The covering rubber 7 is preferably formed using the rubber composition of the present invention.
[0175] The conveyor belt 8 may be made of, for example, 50 to 230 steel cords 5 having a diameter of about 2.0 to 9.5 mm, which are obtained by twisting a plurality of strands having a diameter of about 0.2 to 0.4 mm. Generally, the total thickness T of the conveyor belt 8 may be about 10 to 50 mm.
[0176] In addition, the buffer rubber 6 may use, for example, an adhesive rubber that can be bonded to the galvanized steel cord used in a known steel conveyor belt. Specifically, as the buffer rubber, for example, a rubber composition containing natural rubber (NR), nitrile rubber (NBR), styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR), etc. as a rubber component may be used.
[0177] The conveyor belt of the present invention can be manufactured, for example, by placing a cloth layer, steel cord, or core material layer, which is a core material, between unvulcanized rubber sheets molded from the rubber composition of the present invention according to a conventional method, and vulcanizing them by heating and pressing. The vulcanization conditions can be, for example, about 120 to 180° C. and about 0.1 to 4.9 MPa for about 10 to 90 minutes.
[0178] The conveyor belt of the present invention can be used at a temperature of, for example, -30 to +60°C.
[0179] Example
[0180] The present invention will be described in further detail below based on examples.
[0181] The materials, usage amounts, ratios, processing contents, and processing steps shown in the following examples may be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.
[0182] <Manufacturing of rubber composition>
[0183] The components shown in Table 1 below were used in the compositions (parts by mass) shown in the table, and these were mixed using a Banbury mixer at 90 to 180° C. to produce rubber compositions (unvulcanized).
[0184] It should be noted that in Example 5, the mass ratio of the amount of chlorinated paraffin used to the amount of antimony trioxide used (the amount of chlorinated paraffin used / the amount of antimony trioxide used) was 4.0. In Example 7, the mass ratio of the amount of chlorinated paraffin used to the amount of antimony trioxide used was 2.9. The mass ratio of the amount of chlorinated paraffin used to the amount of antimony trioxide used in the Examples and Comparative Examples other than Examples 5 and 7 was 4.2.
[0185] (Production of vulcanized rubber sheets 1 and 2)
[0186] Production of vulcanized rubber sheet 1
[0187] Each rubber composition (unvulcanized) prepared as described above was vulcanized for 30 minutes using a press molding machine at 148° C. at a surface pressure of 3.0 MPa under normal vulcanization conditions to prepare a vulcanized rubber sheet 1 (initial) having a length of 150 mm, a width of 150 mm, and a thickness of 2 mm.
[0188] Production of vulcanized rubber sheet 2
[0189] Each vulcanized rubber sheet 1 produced as described above was subjected to an aging test at 70° C. for 168 hours to produce a vulcanized rubber sheet 2 after aging (after aging).
[0190] <Evaluation>
[0191] The following evaluations were performed using each vulcanized rubber sheet produced as described above. The results are shown in the tables.
[0192] (Abrasion resistance)
[0193] Using the vulcanized rubber sheets 1 and 2 prepared as described above, a wear test (B method) was carried out using a DIN wear tester at 23°C under the conditions of rotation speed [40 rpm], load [9.8 N], and abrasion type [511XP60] in accordance with JIS K6264-2:2005, and the wear amount [mm] of the vulcanized rubber sheets 1 and 2 was measured. 3 ].
[0194] Evaluation criteria for initial wear resistance
[0195] In the present invention, the wear amount of the vulcanized rubber sheet 1 is 90 mm. 3 When the wear amount is less than 90 mm, the initial wear resistance is evaluated as excellent. 3 , the better the initial wear resistance.
[0196] On the other hand, when the wear exceeds 90 mm 3 In the case of , it was evaluated that the initial wear resistance was poor.
[0197] The evaluation results of the wear amount of the vulcanized rubber sheet 1 are shown in the column of “wear resistance BL (initial wear resistance)” in the table.
[0198] Evaluation results of the wear amount of the vulcanized rubber sheet 2
[0199] The evaluation results of the wear amount of the vulcanized rubber sheet 2 are shown in the column of “Abrasion resistance AG (wear amount of the vulcanized rubber sheet 2)” in each table.
[0200] (Flame retardancy)
[0201] ·Test piece preparation
[0202] Using each rubber composition produced as described above, test pieces (6 test pieces each) were produced according to JIS K6324:2013 "Flame retardant performance conveyor belt - Grades and test methods (Flame retardant performance conveyor belt - Grades and test methods)" 7.2.1. Vulcanization during the above production was performed in the same manner as the production of the vulcanized rubber sheet 1, using a press molding machine at 148°C, and vulcanization was performed under normal vulcanization conditions at a surface pressure of 3.0 MPa for 30 minutes to obtain a BL sample (blank sample).
[0203] Three of the six BL samples obtained as described above were used to perform an aging test in which they were left to stand at 70° C. for 168 hours, thereby obtaining samples after the aging test.
[0204] Evaluation method of flame retardancy
[0205] The duration of flame (unit: seconds) was measured for the BL sample and the sample after the aging test in accordance with JIS K6324:2013 “Flame retardant performance conveyor belts - Grades and test methods (Flame retardant performance conveyor belts - Grades and test methods)”.
[0206] Evaluation criteria for initial flame retardancy
[0207] In the present invention, when the BL sample (blank sample) satisfies the JIS 3 grade flame retardancy test standard [the duration of the flame is 60 seconds or less (the duration of the flame is the average value of 3 test pieces), and there is no reburning], it is evaluated as having excellent initial flame retardancy, which is represented by "0".
[0208] In the case where the BL sample (blank sample) did not satisfy the flame retardancy test standard of JIS Class 3, it was evaluated that the initial flame retardancy was poor, which was indicated by "×".
[0209] The evaluation results of the flame retardancy of the BL sample are shown in the column of “Flame retardancy BL (initial flame retardancy)” in the table.
[0210] In addition, the evaluation of the flame retardancy of the samples after the aging test will be described later.
[0211] (Maintenance of physical properties after aging)
[0212] ΔTB, ΔEB
[0213] A test piece was prepared by punching out a JIS No. 3 dumbbell-shaped rubber sheet piece from each of the vulcanized rubber sheets 1 and 2 prepared as described above. Using the test piece, a tensile test was carried out at a tensile speed of 500 mm / min at 23°C in accordance with JIS K6251:2017, and the TB (tensile strength at break) and EB (elongation at break) of the vulcanized rubber sheets 1 and 2 were measured. The obtained values were substituted into the following formula to calculate ΔTB (%) and ΔEB (%).
[0214] ΔTB (%) = (TB of vulcanized rubber sheet 2 - TB of vulcanized rubber sheet 1) / TB of vulcanized rubber sheet 1 × 100
[0215] ΔEB (%) = (EB of vulcanized rubber sheet 2 - EB of vulcanized rubber sheet 1) / EB of vulcanized rubber sheet 1 × 100
[0216] ·ΔHS
[0217] Using each vulcanized rubber sheet 1, 2 prepared as described above, a type A durometer hardness test was performed at 25°C in accordance with JIS K6253-3:2012 to measure the hardness of the vulcanized rubber sheets 1, 2, and the obtained value was substituted into the following formula to determine ΔHS (%).
[0218] ΔHS (%) = (HS of vulcanized rubber sheet 2 - HS of vulcanized rubber sheet 1) / HS of vulcanized rubber sheet 1 × 100
[0219] Evaluation criteria for maintaining wear resistance after aging
[0220] The wear amount of the vulcanized rubber sheet 1 is 90 mm. 3 The wear amount of the vulcanized rubber sheet 2 is 100 mm or less (i.e., the initial wear resistance is excellent). 3 In the case below, it is evaluated that the wear resistance after aging is excellent. In the above case, the wear amount of the vulcanized rubber sheet 2 is less than 100 mm. 3 , the better the maintenance of wear resistance after aging (or the wear resistance after aging).
[0221] On the other hand, although the wear amount of the vulcanized rubber sheet 1 is 90 mm 3 Below, but the wear amount of the vulcanized rubber sheet 2 exceeds 100mm 3 In the case of , it was evaluated that the maintenance of wear resistance after aging was poor.
[0222] Evaluation method for maintaining flame retardancy after aging
[0223] When the flame duration (unit: seconds) of the sample after the aging test evaluated in accordance with JIS K6324:2013 "Flame retardancy performance conveyor belt-grade and test method" as described above meets the JIS 3 grade flame retardant test standard [the flame duration is 60 seconds or less (the flame duration is the average value of 3 test pieces), and there is no re-burning], it is evaluated that the flame retardancy after aging is excellent, which is indicated as "○".
[0224] On the other hand, when the duration of flame (unit: seconds) of the sample after the aging test did not satisfy the flame retardancy test standard of the JIS Class 3, the flame retardancy after aging was evaluated as poor and indicated as "×".
[0225] The evaluation results of the flame retardancy of the samples after the aging test are shown in the column of “Flame retardancy AG (sample after aging test)” in the table.
[0226] Evaluation criteria for maintaining flame retardancy after aging
[0227] When the initial flame retardancy is excellent (indicated by "○" in the "Flame Retardancy BL (...)" column in the table) and the flame retardancy after aging is excellent (indicated by "○" in the "Flame Retardancy AG (...)" column in the table), it is evaluated that the flame retardancy after aging is excellent.
[0228] On the other hand, when the initial flame retardancy is excellent (the "Flame retardancy BL (...)" column in the table is "○"), but the flame retardancy after aging is poor (the "Flame retardancy AG (...)" column in the table is "×"), it is evaluated that the flame retardancy maintenance after aging is poor.
[0229] (Evaluation criteria for maintenance of physical properties after aging)
[0230] In the present invention, when the above ΔTB is within ±20%, ΔEB is within ±20%, and ΔHS is within ±8%, the above wear resistance after aging is excellently maintained, and the above flame retardancy after aging is excellently maintained, it is evaluated that the maintenance of physical properties after aging is excellent.
[0231] On the other hand, in at least one of the cases corresponding to the above-mentioned ΔTB being outside the range of ±20% (exceeding +20% or less than -20%), the case where ΔEB being outside the range of ±20%, the case where ΔHS being outside the range of ±8%, the case where the maintenance of the wear resistance after aging is poor, and the case where the maintenance of the flame retardancy after aging is poor, it is evaluated that the maintenance of the physical properties after aging is poor.
[0232] [Table 1]
[0233]
[0234] [Table 2]
[0235]
[0236]
[0237] [Table 3]
[0238] [Table 4]
[0239]
[0240] The details of each component shown in each table are as follows.
[0241] (Rubber component, diene rubber)
[0242] NR: Natural rubber. RSS#3
[0243] BR: Butadiene rubber. Trade name: Nipol BR1220 (weight average molecular weight: 460,000, manufactured by Nippon Zeon Co., Ltd.)
[0244] (Carbon Black)
[0245] ·ISAF grade CB: Trade name: Sewtrulding N220, manufactured by Kempinski Co., Ltd. N2SA: 111m 2 / g, DBP: 115cm 3 / 100g
[0246] ·HAF-grade CB: Trade name: シーストN, manufactured by Shin-Nichi Chemical Co., Ltd. N2SA: 74m 2 / g, DBP: 101cm 3 / 100g
[0247] (Flame Retardant)
[0248] Chlorinated paraffin: Enpara 70S manufactured by Dober Chemika Co., Ltd. (trade name). Chlorine content 68 to 72% by mass. Average Cl content 70% by mass. The chlorine content in the chlorinated paraffin was calculated using the average Cl content of 70% by mass.
[0249] · Antimony trioxide: PATOX-M manufactured by Nippon Seiko Co., Ltd. (trade name)
[0250] (Amine compounds)
[0251] RD (weight average molecular weight: 400-600): trimethyldihydroquinoline compound. A polymer of 2,2,4-trimethyl-1,2-dihydroquinoline (structure shown below). Trade name: Nonflux RD (manufactured by Seiko Chemical Co., Ltd.). Weight average molecular weight: 400-600
[0252]
[0253] AD-F (molecular weight: 394): diphenylamine compound. Octylated diphenylamine (structure shown below). Trade name: Noccrack AD-F (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.). Molecular weight: 394
[0254]
[0255] (Antioxidant)
[0256] 6C (molecular weight: 268): amine antioxidant. N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (structure shown below). Trade name: Ozonone 6C (manufactured by Seiko Chemical Co., Ltd.). 6C has the following structure and a molecular weight of 268, so it does not correspond to the specified amine compound.
[0257]
[0258] AW (molecular weight: 217): 6-ethoxy-1,2-dihydro-2,2,4-trimethylquinoline (structure shown below). Trade name: Nocru AW (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.). AW has the following structure and has a molecular weight of 217, so it does not correspond to the specified amine compound.
[0259]
[0260] (additive)
[0261] Wax: paraffin wax. Trade name: OZOACE-0037 (manufactured by Nippon Seira Co., Ltd.)
[0262] Zinc oxide: Zinc oxide. Trade name: "Oxidized lead 3" (manufactured by Shodo Chemical Industry Co., Ltd.).
[0263] · St: stearic acid. Trade name: "Stearic acid 50S" (manufactured by Chiba Fatty Acid Co., Ltd.)
[0264] (Vulcanization accelerator)
[0265] Vulcanization accelerator CZ: N-cyclohexyl-2-benzothiazolylsulfenamide (trade name: Noxela CZ, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0266] Vulcanization accelerator D: diphenylguanidine (trade name: Noxela D, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0267] Vulcanization accelerator DM: dibenzothiazyl disulfide (trade name: Noxelara DM-PO, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0268] Vulcanization accelerator DTDM: 4,4'-dithiomorpholine (trade name: Sanflul R, manufactured by Sanshin Chemical Industry Co., Ltd.)
[0269] (Vulcanizing agent)
[0270] Sulfur: Oil-treated sulfur. Produced by Hosoi Chemical Industry Co., Ltd. Sulfur concentration: 95% by mass. The content shown in the column "Sulfur" in Table 1 is the amount of the oil-treated sulfur.
[0271] From the results in Table 1, it was confirmed that the rubber composition of the present invention exhibited the desired effects.
[0272] On the other hand, in Comparative Example 1, in which the content of natural rubber and butadiene rubber did not meet the prescribed range and did not contain the prescribed amine compound, the initial wear resistance was poor. In addition, the wear amount of the vulcanized rubber sheet 2 (after aging) in Comparative Example 1 was large, and the wear resistance after aging was also poor.
[0273] In Comparative Example 2, which did not contain the prescribed amine compound, the initial flame retardancy was poor. In Comparative Example 2, the flame retardancy of the sample after the aging test was also poor.
[0274] In Comparative Example 3 which did not contain the predetermined amine compound, the maintenance of physical properties (abrasion resistance, ΔEB, flame retardancy) after aging was poor.
[0275] In Comparative Example 4, which did not contain the predetermined amine compound but contained AW, the maintenance of physical properties (ΔEB, flame retardancy) after aging was poor.
[0276] In Comparative Example 5 in which the mass ratio of the content of the amine compound / the amount of chlorine in the chlorinated paraffin was less than 0.10, the maintenance of physical properties (flame retardancy) after aging was poor.
[0277] In Comparative Example 6, in which the mass ratio of the content of the amine compound / the amount of chlorine in the chlorinated paraffin exceeded 0.60, the initial wear resistance and the maintenance of physical properties (ΔHS) after aging were poor. In addition, in Comparative Example 6, the wear amount of the vulcanized rubber sheet 2 (after aging) was large, and the wear resistance after aging was also poor.
[0278] In Comparative Example 7, in which the mass ratio of the content of the amine compound / the amount of chlorine in the chlorinated paraffin was less than 0.10, the maintenance of physical properties (abrasion resistance, ΔEB, flame retardancy) after aging was poor.
[0279] Explanation of symbols
[0280] 1: Fabric layer
[0281] 2: Coating rubber
[0282] 3,7: Covering rubber
[0283] 4, 8: Conveyor belt
[0284] 5: Steel cord
[0285] 6: Buffer rubber.
Claims
1. A rubber composition comprising: a diene rubber comprising natural rubber and butadiene rubber, a flame retardant comprising chlorinated paraffin and antimony trioxide, an amine compound comprising a trimethyldihydroquinoline compound having a weight average molecular weight of 300 or more and / or a diphenylamine compound having a molecular weight of 300 or more, carbon black, sulfur, and a vulcanization accelerator, The content of the natural rubber is 30 to 60% by mass of the total amount of the diene rubber. The content of the butadiene rubber is 40 to 70% by mass of the total amount of the diene rubber. The content of the chlorinated paraffin is 20 to 35 parts by mass based on 100 parts by mass of the diene rubber. The content of the antimony trioxide is 5 to 12 parts by mass based on 100 parts by mass of the diene rubber. The mass ratio of the content of the amine compound relative to 100 parts by mass of the diene rubber / the amount of chlorine in the chlorinated paraffin relative to 100 parts by mass of the diene rubber is 0.10 to 0.
60.
2. The rubber composition according to claim 1, wherein the content of the natural rubber is 40 to 55% by mass of the total amount of the diene rubber. The content of the butadiene rubber is 45 to 60% by mass in the total amount of the diene rubber.
3. The rubber composition according to claim 1, wherein the carbon black has a nitrogen adsorption specific surface area exceeding 100 m 2 / g and the oil absorption of dibutyl phthalate is 100~140cm 3 / 100g of carbon black 1. 4 . The rubber composition according to claim 1 , wherein the content of the carbon black is 40 to 60 parts by mass based on 100 parts by mass of the diene rubber.
5. The rubber composition according to claim 1, wherein the content of the chlorinated paraffin is 23 to 30 parts by mass based on 100 parts by mass of the diene rubber. The content of the antimony trioxide is 5 to 10 parts by mass based on 100 parts by mass of the diene rubber. 6 . The rubber composition according to claim 1 , wherein the amine compound includes the trimethyldihydroquinoline compound. The rubber composition according to claim 1 , further comprising an antioxidant. The rubber composition according to claim 1 , which is for a conveyor belt. 9 . A conveyor belt produced using the rubber composition according to claim 1 .